2019
DOI: 10.1186/s13102-019-0130-z
|View full text |Cite
|
Sign up to set email alerts
|

Kettlebell training in clinical practice: a scoping review

Abstract: Background A scoping review of scientific literature on the effects of kettlebell training. There are no authoritative guidelines or recommendations for using kettlebells within a primary care setting. Our review objectives were to identify the extent, range and nature of the available evidence, to report on the types of evidence currently available to inform clinical practice, to synthesise key concepts, and identify gaps in the research knowledge base. Methods Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 116 publications
1
22
0
2
Order By: Relevance
“…A properly designed resistance training program for older adults, includes multi-joint exercises such as the kettlebell swing and kettlebell deadlift, is individualised, periodised, progressive, and includes appropriate technique instruction (Fragala et al 2019). A review (Meigh et al 2019) was unable to identify descriptive data of kettlebell exercises from older adults for any of these variables. Results of the present study allow healthcare providers to make a more informed decision about whether, and how to use the kettlebell swing as a therapeutic exercise for older adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A properly designed resistance training program for older adults, includes multi-joint exercises such as the kettlebell swing and kettlebell deadlift, is individualised, periodised, progressive, and includes appropriate technique instruction (Fragala et al 2019). A review (Meigh et al 2019) was unable to identify descriptive data of kettlebell exercises from older adults for any of these variables. Results of the present study allow healthcare providers to make a more informed decision about whether, and how to use the kettlebell swing as a therapeutic exercise for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted May 17, 2021. ; https://doi.org/10.1101/2021.05.17.444430 doi: bioRxiv preprint A recent review (Meigh et al 2019) identified no standards or guidelines to inform healthcare providers of how to use kettlebells safely and confidently with older adults. Additionally, current resistance training guidelines for older adults (Borde et al 2015;Fragala et al 2019;Lopez et al 2017) do not translate to hardstyle kettlebell practices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Популярность гиревого спорта особенно возросла в минувшем десятилетии. Это отражается в результатах научных исследований как в нашей стране [1,2], так и во всем мире [3,4] Цель исследования: определение степени сопряженности показателей вертикальной реакции опоры (R(t)_верт) и вертикальной составляющей ускорения туловища (а(t)_верт) во время выполнения упражнения гиревого спорта «толчок». Для того чтобы определить амплитудные значения силы F(t), действующей на туловище в вертикальном направлении в характерных точках a, b, c, …, i, необходимо ускорение в этих точках умножить на массу «М» системы «спортсмен -гиря»: F(t) = а(t)_верт *M. В таблицу, приведенную ниже, включены известные данные ускорения а(t)_верт и R(t)_верт из рис.…”
Section: Abstract: Kettlebell Lifting Competitive Exercise «Jerk» Funclassified